Amidst tongues tearing apart and lying lips, God of and for the oppressed: Casting an African gaze at Psalm 12 - Masenya, Madipoane (Stellenbosch Theological Journal, 2016)
If there is any piece of literature that seems to be time-less, allowing each reader from different cultural contexts and time periods to break through it, it is the Psalter. Also, the struggle by the scholars to lay handle on the origins of the individual lament/complaint psalms may prove affirming to those, who on account of their marginal status, could be “barred” from reading the psalms informed by their own marginal status. Psalm 12 seems to defy clear categorization both as an individual or a communal lament. Like others, it is a psalm that critiques the abusive use of the human organs that enable speech that is, the tongue and the lips. Particularly when the preceding organs are used by the powerful (read: the rich) to despoil the poor and needy, YHWH, the God, of and for the oppressed gets roused and acts in their favour! If re-read African-consciously, what kind of reading may Psalm 12 yield?